2004
DOI: 10.1016/s0736-0266(03)00153-0
|View full text |Cite
|
Sign up to set email alerts
|

PGE2 and IL‐6 production by fibroblasts in response to titanium wear debris particles is mediated through a Cox‐2 dependent pathway

Abstract: Aseptic loosening of orthopaedic implants is precipitated by wear debris-induced osteolysis. Central to this process are the proinflammatory mediators that are produced in response to wear by the fibroblastic cells, which comprise the majority of periprosthetic membranes. Since this pro-inflammatory cascade is mediated by a plethora of factors with redundant functions, it is imperative to establish a hierarchy. Two well-known fibroblast derived pro-inflammatory factors that stimulate wear debris-induced osteoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 35 publications
3
46
0
Order By: Relevance
“…[40][41][42] Our data clearly indicate that COX-2 is also important in resorption associated with focal, directed remodeling in response to fatigue injury. Ibuprofen also inhibited lamellar bone formation within the resorption spaces along the fracture line.…”
Section: Discussionmentioning
confidence: 54%
“…[40][41][42] Our data clearly indicate that COX-2 is also important in resorption associated with focal, directed remodeling in response to fatigue injury. Ibuprofen also inhibited lamellar bone formation within the resorption spaces along the fracture line.…”
Section: Discussionmentioning
confidence: 54%
“…Previous studies have also reported that fibroblasts are capable of phagocytosing wear debris and secreting cytokines and RANKL to support osteoclast formation and bone resorption (Bukata et al 2004, Horiki et al 2004. Osteoclastogenesis supported by other sources of fibroblasts happened only in the presence of osteoclastogenic factors other than just M-CSF (such as dexamethasone), while pseudomembrane-derived fibroblasts were able to support osteoclastgenesis and bone resorption only in the presence of M-CSF.…”
Section: Osteoclast Formation and Activitymentioning
confidence: 96%
“…Not only the fibroblasts from synovium and pseudocapsule (Sakai et al 2002, Mandelin et al 2005b), but also the fibroblasts from skin, spleen and respiratory diaphragm (Quinn et al 2000) have been reported to be able to secrete RANKL and support bone resorption. Using a mouse model, Bukata et al (2004) also proved that fibroblasts could phagocytose particles, which resulted in an increase in the secretion of proinflammatory cytokines. We therefore hypothesized that fibroblasts may play an important role in periprosthetic osteolysis, and that bone cement particles might stimulate secretion of sRANKL as well as other osteoclastogenic factors in fibroblasts, thus contributing to prosthetic osteolysis.…”
mentioning
confidence: 92%
“…monocytes), DC remain viable when irradiated [37]. This is because DC (but not classical monocytes) have constitutively active DNArepair systems that repair double-strand DNA-breaks [38].…”
Section: Irradiated DC Maintain Their Ability To Stimulate Fibroblastsmentioning
confidence: 99%